2009
DOI: 10.1172/jci36628
|View full text |Cite
|
Sign up to set email alerts
|

Tumor emergence is sensed by self-specific CD44hi memory Tregs that create a dominant tolerogenic environment for tumors in mice

Abstract: Early responses of Tregs and effector T cells (Teffs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
128
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 76 publications
13
128
0
4
Order By: Relevance
“…33 Several reports revealed that effector/memory Treg have the suppressive activity superior to that of naive Treg 23 and exhibit a high proliferation rate. 22 , 34 Moreover, it has been shown that this compartment contains a substantial proportion of self-specific T cells susceptible to recruitment and activation by tumor self-antigens. 22 , 35 Therefore, the infiltration of Panc02 tumors with effector/memory Treg cells may be largely responsible for the inability of the immune system to reject the tumor, suggesting a Treg depletion as a possible therapeutic strategy for the pancreatic cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Several reports revealed that effector/memory Treg have the suppressive activity superior to that of naive Treg 23 and exhibit a high proliferation rate. 22 , 34 Moreover, it has been shown that this compartment contains a substantial proportion of self-specific T cells susceptible to recruitment and activation by tumor self-antigens. 22 , 35 Therefore, the infiltration of Panc02 tumors with effector/memory Treg cells may be largely responsible for the inability of the immune system to reject the tumor, suggesting a Treg depletion as a possible therapeutic strategy for the pancreatic cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 Therefore, we asked if Panc02 tumors could elicit effector T cell response and/or mobilization of memory cells. In spleens of tumor-bearing mice, we detected a significant expansion of the effector/effector memory cell compartment …”
Section: Dominance Of Effector/memory Cells In the Pdac Tumorsmentioning
confidence: 99%
“…Although other types of suppressive cell have been identified, most regulatory T cells are characterized by expression of surface CD25 and by intracellular FOXP3, a transcription factor that mediates many of their inhibitory capabilities (Fontenot et al, 2005). It is unclear what proportion of Tregs react with specificity to tumour antigens (Wang et al, 2005), or whether they are recruited through the recognition of shared self-antigens that are co-expressed by tumour cells (Nishikawa et al, 2003;Darrasse-Jeze et al, 2009). Tregs can inhibit effector T-cell responses during both the induction (Darrasse-Jeze et al, 2009) and the effector stages (Huehn et al, 2004;Sarween et al, 2004) by a number of mechanisms, such as through direct ligation of CTLA-4 with CD80 or CD86 on effector T cells, by promoting the development of inhibitory DCs, or through the generation of inhibitory cytokines, transforming growth factor-b and IL10 (von Boehmer, 2005).…”
Section: Suppression By Regulatory T Cellsmentioning
confidence: 99%
“…Parce que ces derniers réagissent en permanence aux antigènes du soi exprimés par les cellules tumorales comme par les cellules normales et que leur réponse est donc de type « mémoire ». Les Treg sont ainsi mobilisés bien plus rapidement et fortement lors de l'apparition d'une tumeur que ne le sont les lymphocytes T effecteurs qui étaient au repos avant que la tumeur n'apparaisse [14]. Cet avantage crucial des Treg est perdu en cas de vaccination préventive par des TAA.…”
unclassified
“…Cet avantage crucial des Treg est perdu en cas de vaccination préventive par des TAA. Les T effecteurs mémoires apparaissent alors résistants à la suppression qu'induisent les Treg [14]. Les immunothérapies efficaces qui voient le jour aujourd'hui prennent en compte l'inhibition de la réponse régulatrice cellulaire soit en la bloquant, soit en générant des cellules mémoires résistantes à son inhibition.…”
unclassified